On the Interpretation and Correlation of High‐Temperature Ignition Delays in Reactors with Varying Thermodynamic Conditions. Issue 6 (6th April 2018) - Tao, Mingyuan; Laich, Andrew; Lynch, Patrick; Zhao, Peng
ABSTRACT: Ignition delay time (IDT) is a useful global metric for fuel performance screening and a major target for kinetic modeling. Measurements of IDT are conceptually straightforward; however, interpretation could be complicated, especially for systems with changing temperature and pressure. Some experimental conditions in the high repetition rate miniature shock tube (HRRST) exhibit complex temperature and pressure state histories. To better interpret and correlate IDTs, especially those obtained in reactors with varying thermodynamic conditions, an inverse Livengood–Wu (L‐W) integral technique is applied to deconvolve the constant condition IDTs from measured IDTs in the HRRST using information on the varying state history. In this paper, the approximate problem is demonstrated using only the measured pressure history leading up to ignition, where the temperature history is estimated based on an isentropic assumption. The IDTs of several fuels were first measured in the HRRST including isooctane and acetone to represent those fuels without strong low‐temperature chemistry effects. Based on the measured pressure and approximated temperature history, measurements of IDTs in the HRRST compare very favorably with those measured using more conventional techniques, including conventionally sized shock tubes, via the inverse L‐W correlation with relaxed Newton iteration and genetic algorithm. This study demonstrates the feasibility of using a high throughput ignition testing facility, like the HRRST to extract the constant state IDT measured in regular shock tubes, assisted by the inverse L‐W correlation. It is expected with an independent temperature measurement available in the future, IDTs in a broader range of thermodynamic conditions and effects of heat loss could be better resolved.